2018
DOI: 10.1089/neu.2018.5684
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Abnormalities within Normal Appearing Tissue in Chronic Traumatic Brain Injury

Abstract: Magnetic resonance imaging (MRI) is a powerful tool for visualizing traumatic brain injury(TBI)-related lesions. Trauma-induced encephalomalacia is frequently identified by its hyperintense appearance on fluid-attenuated inversion recovery (FLAIR) sequences. In addition to parenchymal lesions, TBI commonly results in cerebral microvascular injury, but its anatomical relationship to parenchymal encephalomalacia is not well characterized. The current study utilized a multi-modal MRI protocol to assess microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 56 publications
(66 reference statements)
4
29
0
Order By: Relevance
“…Taken together, these data suggest a model wherein TH and TVI are distinct injury patterns, and not simply a continuum of bleeding diathesis, with TVI representing a more “mild” bleeding injury than TH. This is consistent with data from our group showing that, in the chronic state, there can be cerebral vascular dysfunction even in the absence of frank injury from a TBI-related hemorrhage (33, 46).…”
Section: Discussionsupporting
confidence: 93%
“…Taken together, these data suggest a model wherein TH and TVI are distinct injury patterns, and not simply a continuum of bleeding diathesis, with TVI representing a more “mild” bleeding injury than TH. This is consistent with data from our group showing that, in the chronic state, there can be cerebral vascular dysfunction even in the absence of frank injury from a TBI-related hemorrhage (33, 46).…”
Section: Discussionsupporting
confidence: 93%
“…Although CVR deficit is a symptom of many neurodegenerative diseases, 23,54,55 recent work by Diaz-Arrastia et al 7,17,56,57 has demonstrated global, Figure 7. ELISA measurement of aSMA concentration in cortical vascular-enriched fractions at three months and nine months post-injury.…”
Section: Discussionmentioning
confidence: 99%
“…For example, altered cerebral blood flow (CBF), cerebrovascular reactivity, and blood–brain barrier permeability have been observed in both the acute and chronic phases of injury following all severities of TBI. 1316 Importantly, this prolonged cerebrovascular dysfunction not only directly negatively influences cognitive and behavioral functioning, but independently initiates degenerative processes within the brain. 10,11 Indeed, we recently showed that lower CBF is associated with reduced axonal integrity in middle-aged Veterans with history of mild or moderate TBI.…”
Section: Introductionmentioning
confidence: 99%